Reduced T-Helper 17 Responses to Streptococcus pneumoniae in Infection-Prone Children Can Be Rescued by Addition of Innate Cytokines. (13th February 2017) - Basha, Saleem; Kaur, Ravinder; Mosmann, Tim R.; Pichichero, Michael E.
Message: Children experience frequent infections by pneumococci. T-helper (Th) 17 cells are known to play an important role in Streptococcus pneumoniae clearance. We show reduced Th17 responses to pneumococci in peripheral blood mononuclear cells of infection-prone children that can be rescued by addition of Th17-promoting cytokines. Abstract: Background: T-helper (Th) 17 cells are important in the control of Streptococcus pneumoniae. We sought to understand the mechanism of failure of Th17 immunity resulting in S. pneumoniae infections in children <2 years old. Methods: Peripheral blood mononuclear cells (PBMCs) from infection-prone (IP) and non-IP (NIP) children 9–18 months old were examined for their responses to heat-killed S. Pneumoniae, using flow cytometry, reverse-transcription polymerase chain reaction, and enzyme-linked immunoassay. We measured cytokine production, proliferation, and differentiation of Th17 cells and the expression of transcription factors in response to S. pneumoniae . Results: PBMCs of IP children stimulated with heat-killed S. pneumoniae had significantly reduced percentages of CD4 + Th1 (interleukin2, tumor necrosis factor α) and Th17 (interleukin 17A) cells compared with NIP children. Addition of exogenous Th17-promoting cytokines (interleukin 6, 1β, and 23 and transforming growth factor β) restored CD4 + Th17 cell function in cells from IP children to levels measured in NIP children. Conclusions: Reduced Th17 responses to S. pneumoniae in PBMCs of IP children can be rescued by addition of Th17-promoting cytokines.